Performance of maximum number of repetitions with cluster-set configuration - Iglesias-Soler, E.; Carballeira, E.; Sánchez-Otero, T.; Mayo, X.; Fernández-del-Olmo, M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To analyze performance during the execution of a maximum number of repetitions (MNR) in a cluster-set configuration. Method: Nine judokas performed 2 sessions of parallel squats with a load corresponding to 4-repetition maximum (4RM) with a traditional-training (TT) and cluster-training (CT) set configuration. The TT consisted of 3 sets of repetitions leading to failure and 3 min of rest between sets. In the CT the MNR was performed with a rest interval between repetitions (45.44 ± 11.89 s). The work-to-rest ratio was similar for CT and TT. Results: MNR in CT was 45.5 ± 32 repetitions and was 9.33 ± 1.87 times the volume in TT. There was a tendency for the average mean propulsive velocity (MPV) to be higher in CT (0.39 ± 0.04 vs 0.36 ± 0.04 m/s for CT and TT, respectively, P = .054, standardized mean difference [d] = 0.57). The average MPV was higher in CT for a similar number of repetitions (0.44 ± 0.08 vs 0.36 ± 0.04 m/s for CT and TT, respectively, P = .006, d = 1.33). The number of repetitions in TT was correlated with absolute 4RM load (r = -.719, P = .031) but not in CT (r = -.273, P = .477). Conclusions: A cluster-set configuration allows for a higher number of repetitions and improved sustainability of mechanical performance. CT, unlike TT, was not affected by absolute load, suggesting an improvement of training volume with high absolute loads.